Current dietary approaches in ulcerative colitis: Exploring implications for women’s health: Nutritional care for ulcerative colitis and women’s health - Mumcu, Mine; Kavsara, Hasan Kaan (Journal of Surgery and Medicine, 2024)
Ulcerative colitis (UC) affects many individuals, significantly impacting their quality of life (QoL) and leading to severe medical complications. Unfortunately, the adverse health outcomes of UC are often overlooked, particularly in relation to women's health, including pregnancy, lactation, sexuality, and menopause. The main objective of this review is to provide guidance for women with UC, helping them navigate their disease and gain knowledge about the effects of nutrition on their overall well-being. A literature search was conducted between October 1, 2022, and July 14, 2023, using books, documents, and journal articles. Internet-based sites such as PubMed, ScienceDirect, EBSCO, and Google Scholar were also utilized. It became evident that women with UC are greatly affected during active periods of the disease, which can significantly reduce their QoL. Pregnancy, sexuality, menstruation, and puberty were among the factors most negatively impacted by the disease. A diet rich in anti-inflammatory foods, probiotics, berberine, turmeric, and vitamin D was found to have a positive association with UC. However, the consumption of a Western dietary pattern or a meat-based diet increases the risk of the disease. In conclusion, maintaining remission and following dietary patterns that suppress inflammation may help reduce complications and improve QoL in women. Our data suggest that all women diagnosed with UC should be well-informed and educated about the disease and its consequences. Further studies are needed to investigate the relationship between ongoing dietary habits and the treatment of UC in women.